Decorin‐PEI nanoconstruct attenuates equine corneal fibroblast differentiation. (30th May 2013) - Donnelly, Kevin S.; Giuliano, Elizabeth A.; Sharma, Ajay; Tandon, Ashish; Rodier, Jason T.; Mohan, Rajiv R.
Abstract Objective To explore (i) the potential of polyethylenimine (PEI) nanoparticles as a vector for delivering genes into equine corneal fibroblasts (ECFs) using green fluorescent protein (GFP) marker gene, (ii) whether PEI nanoparticle‐mediated decorin (DCN) gene therapy could be used to inhibit fibrosis in the equine cornea using an in vitro model. Procedure Polyethylenimine–DNA nanoparticles were prepared at nitrogen‐to‐phosphate (N‐P) ratio of 15 by mixing 22 kDa linear PEI and a plasmid encoding either GFP or DCN. ECFs were generated from donor corneas as previously described. Initially, GFP was introduced into ECFs using PEI nanoparticles to confirm gene delivery, then DCN was introduced to evaluate for antifibrotic effects. GFP gene delivery was confirmed with real‐time qPCR and ELISA. Changes in fibrosis after DCN therapy were quantified by measuring α‐smooth muscle actin (αSMA) mRNA and protein levels with qPCR, immunostaining, and immunoblotting. Cytotoxicity was determined by evaluating cell morphology, cellular viability, and TUNEL assay. Results Polyethylenimine‐green fluorescent protein‐treated cultures showed 2.2 × 104 GFP plasmid copies/μg of cellular DNA and 2.1 pg of GFP/100 μL of lysate. PEI–DCN delivery significantly attenuated TGFβ‐induced transdifferentiation of fibroblasts to myofibroblasts (2‐fold decrease of αSMA mRNA; P = 0.05) and significant inhibition of αSMA (49 ± 14.2%; P < 0.001) in immunocytochemical staining and immunoblotting were found. Furthermore, PEI–DNA nanoparticle delivery did not alter cellular phenotype at 24 h and cellular viability was maintained. Conclusions Twenty‐two kilo dalton Polyethylenimine nanoparticles are safe and effective for equine corneal gene therapy in vitro. PEI‐mediated DCN gene delivery is effective at inhibiting TGFβ‐mediated fibrosis in this model.